Tinjauan Yuridis Tindak Pidana Pencucian Uang di Industri Fintech - Gotman Tambunan; Kartina Pakpahan; Nikodemus Ariandy Manik; Timothy Pamungkas Situmorang (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The development of technology and information systems in the financial sector has changed people's habits inefficient financial transactions. The method used the normative legal method, the aim of analyzing the legal arrangements for money laundering criminals in the Fintech Industry. The results of the research is regulation of money laundering is the provisions of Law No. 8 of 2010 articles 3, 4 and 5, Law No. 11 of 2008 as amended into Law No. 19 of 2016 articles 29 and 32, Then, the Draft Criminal Code is contained in articles 607, 608 and 609, if more than one money laundering regulation, the more specific regulation is used, namely in the Fintech Industry, as with the application of the principle of lex specialis derogat legi generalis, prevention of money laundering through repressive and preventive measures. There is prevention of money laundering in the Fintech Industry by the Financial Services Authority (OJK) by issuing circular letter no. 6/ SE OJK. 05/2021. Every perpetrator of money laundering in the Fintech Industry, can be accountable for the actions if there is an element of error consisting of intentional and negligence.